NEW TASKS AND FUNCTIONS OF THE TEACHER OF INNOVATIVE TYPE IN THE PREPARATION OF THE COMPETENT DOCTOR - Tkachuk, Elena; Kulbashna, Yaroslava; Zakharova, Valeriia (Educological discourse, 2018)
The article reveals the roles and functions of the modern teacher of higher medical educational establishment (instructor, trainer, tutor, mentor, coach, facilitator, manager, researcher) in creating high-quality experience for students and ensuring conditions for their knowledge acquisition, competencies and skills. It was substantiated the necessity of updating the pedagogical paradigm in the higher medical school according to evolutionary personal changes of the modern youth generation. It is also established that future doctors’ healthcare and foreign language competencies formation are not evaluated adequately among the university teachers’ functions. The key tasks of the modern medical university teachers, which are interrelated and interdependent with each other, are determined.